2019
DOI: 10.1111/jav.02032
|View full text |Cite
|
Sign up to set email alerts
|

At sea vocal repertoire of a foraging seabird

Abstract: Seabirds spend most of their time at sea, yet our knowledge of their activities and behaviour is limited due to difficulties of in‐situ data collection. In particular, we know virtually nothing about their acoustic communication when at sea. We benefited from the recent development of miniaturised audio‐recording devices to deploy acoustic recorders on breeding Cape gannets Morus capensis to study their vocal activity while foraging. Call sequences were recorded on 1718 occasions, from which acoustic variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Several studies of boobies [ 33 ] and other seabird species exhibiting high foraging site fidelity [ 98 , 99 ] were carried out in highly productive marine environments (temperate regions), where prey distribution is more predictable, while in tropical areas, it has been pointed out that the presence of bathymetric features may be an important variable in increasing site fidelity [ 34 ]. Social cues, by gathering information from previous foraging trips [ 100 ], information transfer at sea [ 18 , 25 , 101 ] and at the colony [ 26 ], have also been suggested to increase site fidelity, however all were from studies in temperate areas. As females simply kept using the same areas, increasing repeatability of foraging parameters compared to the first period, and no important bathymetric features seem to be present or influencing utilized areas, this further suggests that parental involvement during this period, should be a factor explaining sexual segregation [ 13 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of boobies [ 33 ] and other seabird species exhibiting high foraging site fidelity [ 98 , 99 ] were carried out in highly productive marine environments (temperate regions), where prey distribution is more predictable, while in tropical areas, it has been pointed out that the presence of bathymetric features may be an important variable in increasing site fidelity [ 34 ]. Social cues, by gathering information from previous foraging trips [ 100 ], information transfer at sea [ 18 , 25 , 101 ] and at the colony [ 26 ], have also been suggested to increase site fidelity, however all were from studies in temperate areas. As females simply kept using the same areas, increasing repeatability of foraging parameters compared to the first period, and no important bathymetric features seem to be present or influencing utilized areas, this further suggests that parental involvement during this period, should be a factor explaining sexual segregation [ 13 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these species are often found breeding and/ or co-existing in mixed colonies with conspecifics [ 8 , 14 , 17 , 23 , 24 ]. Although this co-existence could lead to inter-specific competition, this may also be an opportunity for foraging information exchange [ 25 , 26 ] to locate ephemeral prey patches in tropical areas, as happens with other conspecifics [ 18 , 27 ]. This could be a potential foraging strategy for individuals to contour their patchily distributed prey, because studies of penguins in different sized colonies, confirmed foraging overlap between individuals of smaller colonies, while individuals from larger colonies segregated in their foraging areas [ 28 ], possibly after causing prey depletion [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…At least one partner per nest was marked using short-term animal marking sticks for individual identification. In addition for some of these nests, a breeding adult was captured using a pole with a hook as part of another study [20] and a couple of breast feathers were plucked for sex identification based on DNA analyses.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we used the indicator “precision” [44] to calculate the number of correct predictions per class (sexes), based on the confusion matrix. We then compared this accuracy of prediction per class to a prediction by chance, calculated as the number of calls in the class (male or female) divided by the total number of calls (following the method in [20]). This allows us to evaluate the strength of the prediction in comparison to a random allocation of class based on occurrences.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have started to describe the use of aerial vocalisations in foraging seabirds. Gannets emit acoustically distinct vocalisations in different behavioural contexts when at sea, suggesting that each of these vocalisations convey distinct information (Thiebault et al, 2016a(Thiebault et al, , 2019. Recent work has also shown that penguins emit vocalisations from the sea surface when commuting, a behaviour possibly associated with group formation and group foraging (Choi et al, 2017;McInnes et al, in press).…”
Section: Introductionmentioning
confidence: 99%